Reliable, high-quality suppression of NMR signals arising from water and macromolecules: application to bio-fluid analysis. Issue 24 (6th November 2019) - Aguilar, Juan A.; Cassani, Julia; Probert, Fay; Palace, Jacqueline; Claridge, Tim D. W.; Botana, Adolfo; Kenwright, Alan M.
Abstract : This paper proposes a family of pulse sequences (the WASTED family) that improves the capabilities of the presat-CPMG pulse sequence traditionally used to suppress signals from water and macromolecules. Abstract : Analysis of metabolites in biofluids using nuclear magnetic resonance often requires the suppression of obscuring signals arising from water and macromolecules. This paper analyses the limitations of the pulse sequence most commonly used to achieve such suppression (presat-CPMG) and proposes new pulse sequences that do not share those limitations. The utility of these improved pulse sequences is demonstrated in a metabolomic study of multiple sclerosis (MS) patients.